Diffraction Radiation Oscillator with Asymmetric Open Resonant System. Part I. Cold Test Results of Open Resonant System - V.S. Miroshnichenko; I.O. Kovalov (Журнал нано- та електронної фізики)
The results of experimental investigations and 2-D modeling of asymmetric open resonant system properties for diffraction radiation oscillator, in which the periodic structure is displaced on the field spot periphery of operating TEM00q-mode, are presented. It was established, that the asymmetric placement of the periodic structure, in double grating form, on the flat mirror of hemispherical open resonator allows to reduce ohmic and diffraction loss of operating TEM00q-mode and significantly extend the bandwidth of the single-mode tuning. The investigations are carried out in 8-mm waveband.